Development of an interactive E-Module based on realistic mathematics education (RME) to enhance students' mathematical reasoning skills on parallel lines and angles - Scristia, Scristia; Herman, Tatang; Sholihat, M. Nuur’aini; Sari, Novita (Universitas Maritim Raja Ali Haji, 2024)
This study aimed to develop an interactive e-module based on the RME approach, focusing on parallel lines and angles. The e-module was designed using a development studies approach with two main stages: preliminary and formative evaluation. These included self-evaluation, expert review, one-to-one trials, small group trials, and field tests. Data were collected through validation sheets, student response questionnaires, pretests, and posttests. The e-module was deemed valid and practical, with average validation scores from experts and students of 4.4 and 4.89, respectively. Furthermore, the effectiveness of the e-module was measured using T-Test and N-Gain analysis, which showed a significant improvement of 38% in students' mathematical reasoning skills. The findings demonstrate that the RME-based interactive e-module is an effective teaching tool for enhancing mathematical reasoning skills, particularly on parallel lines and angles. This e-module provides an alternative solution for teachers to facilitate interactive, context-based, and independent learning, aligning with the demands of 21st-century education. Future research could explore integrating virtual laboratories or GeoGebra software into the e-module and applying it to other mathematical topics, such as angles in polygons.